Circulating platelet‐derived extracellular vesicles correlate with night‐time blood pressure and vascular organ damage and may represent an integrative biomarker of vascular health. Issue 6 (3rd May 2022) - Lugo‐Gavidia, Leslie Marisol; Carnagarin, Revathy; Burger, Dylan; Nolde, Janis M.; Chan, Justine; Robinson, Sandi; Bosio, Erika; Matthews, Vance B.; Schlaich, Markus P.
Abstract: Elevated office blood pressure (BP) has previously been associated with increased levels of circulating extracellular vesicles (EVs). The present study aimed to assess the relationship between levels of platelet derived EVs, ambulatory BP parameters, and pulse wave velocity as a marker of macrovascular organ damage. A total of 96 participants were included in the study. Platelet‐derived extracellular vesicles (pEVs) were evaluated by flow cytometry (CD41+/Annexin v+). BP evaluation included unobserved automated office BP and ambulatory BP monitoring. Carotid‐femoral pulse wave velocity (PWV) was measured as a marker of macrovascular damage. pEVs correlated with nocturnal systolic BP (r = 0.31; p  = .003) and nocturnal dipping (r = ‐0.29; p  = .01) in univariable analysis. Multivariable regression models confirmed robustness of the association of EVs and nocturnal blood pressure ( p  = .02). In contrast, systolic office, 24h‐ and daytime‐BP did not show significant associations with pEVs. No correlations were found with diastolic BP. Circulating pEVs correlated with pulse wave velocity (r = 0.25; p  = .02). When comparing different hypertensive phenotypes, higher levels of EVs and PWV were evident in patients with sustained hypertension compared to patients with white coat HTN and healthy persons. Circulating platelet derived EVs were associated with nocturnal BP, dipping, and PWV. Given that average nocturnal BP is the strongest predictor of CV events, platelet derived EVs may serve as an integrative marker of vascular health, a proposition that requires testing in prospective clinical trials.